(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The concept underlying human rights in not new, although the name is. The ideology of human right stands upon the fact that human dignity must be protected at any cost. Since these rights belong to human beings because of their very existence, they became operative with their birth. Human rights are rights, which belong to a person as a consequence of being human as a means of human dignity.[1] They are a guarantee of nature for human beings. Due to their origin in nature there rights are also called natural rights.[2] When they are given legal or constitutional protection, they are known as fundamental rights.[3] It can therefore, be said that human rights is the protective umbrella which covers all the rights essential for human beings